Portuguese cultural adaptation and validation of the Activities Scale for Kids (ASK) - Daniela Paixão; Luís Manuel Cavalheiro; Rui Soles Gonçalves; Pedro Lopes Ferreira (Jornal de Pediatria, 2016)
Objectives: The main purpose of the current study was to perform the cross cultural adaptation and validation of the Activities Scale for Kids (ASK) both in its capability and performance versions to the European Portuguese language so it can be used in Portugal by healthcare professionals in children from 5 to 15 years of age with functional disabilities related to specific health conditions. Methods: The cross-cultural adaptation of ASK followed the classic sequential methodology for linguistic equivalence. To test its validity, internal consistency, and reproducibility, the Portuguese version of ASK was administered together with the KINDL Questionnaire (KINDL) to 88 children (10 ± 3 years of age) with functional limitations. The test–retest study was conducted two weeks apart. Results: After obtaining the semantic and content validity, the Portuguese version of ASK demonstrated good levels of reproducibility (performance: intraclass correlation coefficient [ICC] = 0.99; capability: ICC = 0.98) and internal consistency (performance: α = 0.98; capability: α = 0.97). The correlations between ASK and KINDL were positive and moderate. Conclusions: The Portuguese version of ASK showed acceptable levels of validity, internal consistency, and reproducibility; the authors recommend its use in clinical settings. Resumo: Objetivos: O principal objetivo deste estudo foi realizar a adaptação transcultural para o português europeu e a validação das versões de capacidade e desempenho da Escala de Atividades para Crianças (Activity Scale for Kids (ASK)), de forma que possa ser utilizada em Portugal por profissionais da saúde com crianças de 5 a 15 anos de idade com deficiências funcionais relacionadas a doenças específicas. Métodos: A adaptação transcultural da ASK seguiu a metodologia sequencial clássica para obter equivalência linguística. Para testar sua validade, coerência interna e reprodutibilidade, a versão em português da ASK foi administrada juntamente com o Questionário KINDL (KINDL) em 88 crianças (10 ± 3 anos de idade) com limitações funcionais. O estudo de teste-reteste foi realizado com um intervalo de duas semanas. Resultados: Após obter a validade semântica e de conteúdo, a versão em português da ASK demonstrou bons níveis de reprodutibilidade (desempenho: coeficiente de correlação intraclasse (CCI) = 0,99; capacidade: CCI = 0,98) e coerência interna (desempenho: α = 0,98; capacidade: α = 0,97). As correlações entre a ASK e o KINDL foram positivas e moderadas. Conclusões: A versão em português da ASK apresentou níveis aceitáveis de validade, coerência interna e reprodutibilidade, e recomendamos seu uso em ambientes clínicos. Keywords: Child, Disability, Performance, Capability, Outcome measures, Palavras-chave: Criança, Deficiência, Desempenho, Capacidade, Medidas dos resultados